1991
DOI: 10.1111/j.1399-3054.1991.tb00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod and temperature on sugars and fructans in leaf blades, leaf sheaths and stems, and roots in relation to growth of Poa pratensis

Abstract: Solhaug, K. A. 1991. Effects of photoperiod and temperature on sugars and fructans in leaf blades, leaf sheaths and stems, and roots in relation to growth of Poa pratensis. Vegetative piants of Poa pratensis L. cv. Holt were cultivated in short days (SD; 8 h summer daylight) and in iong days (LD; 8 h summer daylight + iow intensity extension of 5 (imol m • s ') at 12, 18 and 24°C in one experiment and at 9,12,15 and 18°C in another. Relative growth rate (RGR) as the mean of both experiments and all temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…It is generally accepted that fructans accumulate under conditions that favor photosynthesis but not growth. Poa pratensis accumulates more fructans under SD than in LD without increases in the relative growth rates (Solhaug 1991). According to Solhaug (1991), the rapid increases in growth of this species in the LD plants compared with the SD plants is associated with allocation of more assimilates to leaf blade growth in LD, and to storage as fructans in SD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is generally accepted that fructans accumulate under conditions that favor photosynthesis but not growth. Poa pratensis accumulates more fructans under SD than in LD without increases in the relative growth rates (Solhaug 1991). According to Solhaug (1991), the rapid increases in growth of this species in the LD plants compared with the SD plants is associated with allocation of more assimilates to leaf blade growth in LD, and to storage as fructans in SD.…”
Section: Discussionmentioning
confidence: 99%
“…Poa pratensis accumulates more fructans under SD than in LD without increases in the relative growth rates (Solhaug 1991). According to Solhaug (1991), the rapid increases in growth of this species in the LD plants compared with the SD plants is associated with allocation of more assimilates to leaf blade growth in LD, and to storage as fructans in SD. Our growth analysis showed that the longer the photoperiod, the higher the growth rate of D. antarctica in both control and cold‐acclimation conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the association of growth and fructans, it is generally accepted that fructans accumulate under conditions that favour photosynthesis but not growth, as demonstrated in Poa pratensis growing under SD with respect to LD conditions, where growth rates are higher and fructan contents lower (Solhaug 1991). According to this author, the increases in growth of this species in the long day treatment, compared with the short day treatments, is associated with allocation of more assimilates to leaf blade growth in LD and to storage as fructans in the SD.…”
Section: Introductionmentioning
confidence: 99%